CDM regulations 2007 explained - Joyce, Raymond (Thomas Telford, 2007)
This book provides a comprehensive guide to the obligations of all parties to a construction project under the new CDM Regulations 2007. It gives a detailed analysis of the individual roles of each party and sets out a checklist to assist practitioners in complying with their obligations.